MODEL PEMBELAJARAN INTERAKTIF DENGAN METODE TANYA JAWAB DALAM MENINGKATAN HASIL BELAJAR SISWA DI MADRASAH IBTIDAIYAH - Murtadlo, Ali; Widhyahrini, Khusna (Pascasarjana IAIN Kudus, 2019)
The purpose of the research was to knowing the improvement of students' Learning Outcomes through Interactive Learning Model with the Question and Answer Method. This is a Classroom Action Research, consisted of four stages: planning, action, observation, and reflection. The instrument used is the assessment instrument for the implementation of learning, the initial test question sheet, the first cycle question sheet and second cycle. The data obtained was analyzed descriptively. The results of analysis the learning quality data in the first cycle is 88.07% classified as quality category and the second cycle of learning quality data is 93.03% categorized as very good. The completeness of learning outcomes in cycle 1 is 78.57% classified as unfinished categories and cycle 2 completeness of learning outcomes is 96.43% classified as complete categories. So, it can be concluded that the Interactive Learning Model by using the Question and Answer Method is proven to be able to improve students Learning Outcomes.